Systematic assessment of transcriptomic and metabolic reprogramming by blue light exposure coupled with aging. - Huang, J.; Zhou, F.; Zhou, H.; Zheng, X.; Huo, Z.; Yang, M.; Xu, Z.; Liu, R.; Wang, L.; Wang, X. (PNAS nexus, 2023)
The prevalent use of light-emitting diodes (LEDs) has caused revolutionary changes in modern life, but the potential hazards to health of blue light are poorly understood. N[6]-methyladenosine (m[6]A) is the most prevalent posttranscriptional modification in eukaryotes and can modulate diverse physiological processes by regulating mRNA fate. Here, to understand the effects and molecular mechanisms of daily low-intensity blue light exposure (BLE) and ascertain whether m[6]A methylation plays a role in BLE-induced phenotypes, we constructed a series of Drosophila models under different durations of daily low-intensity BLE and obtained multiomics profiles. Our results revealed that BLE could induce transcriptomic, m[6]A epitranscriptomic, and metabolomic reprogramming in Drosophila along with aging process. Importantly, the m[6]A methylation sites enriched in the 5' untranslated regions (UTRs) of Drosophila transcripts showed strong age specificity and could be altered by BLE. We experimentally validated that aging-related gene Tor and circadian rhythm-related gene per were regulated by 5' UTR-enriched m[6]A methylation. Overall, our study provides a systematic assessment of m[6]A RNA methylome reprogramming by BLE and aging in Drosophila model.